Genotoxic effects of NDMA-contaminated ranitidine on Allium cepa cells and unveiling carcinogenic mechanisms via DFT and molecular dynamics simulation study - Mst. Kusum Kaly; Md Ekhtiar Rahman; Md. Sohel Rana; Uzzal Kumar Acharjee; Khondokar Nasirujjaman (Scientific Reports)
Abstract This study investigated the potential genotoxic and carcinogenic effects of N-nitrosodimethylamine (NDMA), a hazardous compound found in ranitidine formulations that are used to treat excessive stomach acid. The study first examined the effects of NDMA-contaminated ranitidine formulation on Allium cepa root growth and mitotic activity. The results demonstrated dose-dependent decreases in both root growth and mitotic index indicating genotoxicity and cell division disruption. Elevated concentrations of ranitidine correlated with increased chromosomal aberrations indicating genotoxic capabilities. These outcomes underscored that NDMA contaminated ranitidine exposure triggers genotoxicity hampering cell division and inducing chromosomal aberrations. Electronic characteristics of NDMA revealed its electrophilic nature suggesting its capability to create covalent adducts with DNA bases fostering genotoxic and carcinogenic characteristics. Molecular docking analysis showed the interactions of NDMA with DNA including hydrogen bonds and carbon-hydrogen interactions with nucleotide bases forming DNA adducts. Molecular dynamics simulations showcased the dynamic behavior of the DNA-NDMA complex over time with structural fluctuations. Dynamic hydrogen bond fluctuations implied interactive intricacies between solute and solvent molecules. Overall, this study illuminates how NDMA-contaminated ranitidine could trigger DNA damage and potentially contribute to carcinogenesis. It emphasizes the urgency of minimizing exposure to this perilous and hazardous compound.